Neurolaw and the mind-brain problem in practice: The case of psychological immaturity and brain immaturity - Lavazza, Andrea; Corso, Flavia (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2021)
The law today cannot ignore the findings of neurosciences. These are in fact being included in legal codes, as was the case with the recent Dutch juvenile justice reform. Indeed, even when the contribution of neuroscientific evidence appears to be clear and circumscribed, it brings out some very important issues, which are both ontological and epistemological. For now, we do not really know how to solve these issues, but we can proceed with caution, avoiding the extremes of either rejecting or uncritically adopting neuroscientific categories in our legal systems. Since the law is, at least in part, conventional, we could consider an approach like the one proposed by J. Searle, which seeks to combine naturalism and the preservation of mentalistic categories. This position is probably not the most correct one (provided we do not know which is the most correct one), yet it allows us to design a neurolaw that is in tune with science but does not entail a complete legal revolution, taking neuroscience seriously while also maintaining some seemingly indispensable categories of law.